Middle school students’ mathematical representations in mathematics in context tasks on computing chances based on realistic mathematics education - Ratna Sariningsih; Nurjanah (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Mathematical representation plays a crucial role in students’ understanding of probability concepts, particularly in computing chances, which requires coordination among visual, symbolic, and verbal forms. Previous studies indicate that students often rely on procedural calculations without adequately constructing or connecting representations, leading to shallow conceptual understanding. Realistic Mathematics Education (RME) and Mathematics in Context (MiC) tasks offer potential to address this issue by emphasizing contextual modeling and progressive formalization. Aims: This study aims to describe the forms of mathematical representations used by junior high school students and to analyze the interrelationships among visual, symbolic, and verbal representations when solving MiC tasks on computing chances based on RME principles. Method: A qualitative descriptive approach was employed involving 19 eighth-grade students who had participated in RME-based probability instruction. Data were collected through MiC computing chances tests adapted from Holt et al. and analyzed using the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. This percentage is obtained from the rubric score on students' written responses per item which is then averaged. Results: The results showed that visual representation achieved the highest level (60%), followed by symbolic representation (54%), while verbal representation was the weakest (48%). Visual models functioned effectively as model-of contexts, and symbolic representations developed through progressive formalization; however, integration among representations was not optimal due to limited verbal explanation. Conclusion: RME-based MiC tasks effectively support the development of students’ visual and symbolic representations in probability learning. Nevertheless, strengthening students’ verbal representation and reflective communication is essential to enhance the coherence and meaningful integration of multiple mathematical representations.